Multiscale kinetic modelling of materials : proceedings of the symposium "Multiscale Kinetic Modelling of Materials", organised within the EMRS Fall Meeting 2006 held in Warsaw, Poland, 4-8 September 2006 - Kozubski, Rafał, 1955-; Murch, G. E.; Zięba, Paweł (Diffusion and defect data. Solid state phenomena, 2007)
The inspiration for this book was to gather together the efforts of those physicists, materials scientists/engineers and other scientists who are carrying out interdisciplinary research into multiscale modelling of time-evolving phenomena in materials. The resultant collection focuses on the principal topics of: 1. The current development of theoretical and model approaches to structural kinetics (links between quantum electron theories of solids and non-equilibrium thermodynamics); 2. Computer simulations as an effective tool for studying atomistic mechanisms of structural kinetics (Monte Car.